Innovative Teaching Methodologies For Improving Student Learning Outcomes In Contemporary Education - Muh Habibulloh (Ponpes As-Salafiyyah Asy-Syafi'iyyah, 2026)
This study examines how innovative teaching methodologies improve student learning outcomes in contemporary education through active learning, technology-supported instruction, and formative assessment. A qualitative descriptive design was used to explore classroom practices and participant perspectives in three secondary school classrooms involving six teachers and eighteen students. Data were collected through classroom observations, semi-structured interviews, and document analysis, then analyzed using thematic analysis. The findings show that active learning strategies increased student engagement by encouraging participation, collaboration, and purposeful interaction. Technology-supported instruction strengthened conceptual understanding by presenting ideas through visual, interactive, and contextual learning resources that made abstract content easier to understand. Formative assessment practices improved learning outcomes by creating feedback-rich environments that supported reflection, revision, and ongoing instructional adjustment. The discussion indicates that innovative teaching methodologies function effectively when they are aligned with pedagogical goals, student needs, and teacher competence. The study concludes that the integration of active learning, technology-supported instruction, and formative assessment offers a practical framework for improving student learning outcomes and fostering more responsive, student-centered classroom environments in contemporary education.development and institutional support to implement innovative pedagogy effectively.